(untitled) (Indian Journal of Public Health Research & Development, 2020)
A concise report on mentally challenged children was focused on to their health and wellbeing by assessing their somatotype characteristics. For this study 25 (male) participants, age ranging in between 14 - 18 years, trainable and educable mentally challenged without any multiple disabilities were selected from Special School for Mentally Challenged People under Department of Teacher Training & Non-formal Education, Jamia Millia Islamia, New Delhi. Purposive sampling method and Ex-post facto design were applied. By using Heath- Carter Anthropometric Method each subject was somatotyped. Analysis of Data done through SOMATOTYPE (Computer Programs for Somatotype Analysis) to calculate somatotypes, descriptive and comparative statistics and plotting somatocharts with mean, standard deviation. The result clearly indicated that mentally challenged participants have low level of body fat and observed more percentage in mesomorphic and ectomorphic category and it has been observed that they all were having improper skeleto-muscular development, unbalanced lifestyle. So, it is necessary for mentally challenged participants to involve in special physical education program to develop their fitness level.